Availability and quality of primary health care in the compulsory health insurance system in Kazakhstan - Makhabbat Shurenova; Kuralbay Kurakbayev; Tleukhan Abildaev; Aigul Tazhiyeva (Medicinski glasnik, 2023)
Aim: To evaluate patient satisfaction with primary healthcare services and determine effectiveness indicators within Kazakhstan's compulsory health insurance system. Methods: An analytical observational study with cross-examination was conducted in Kazakhstan's primary healthcare (PHC) organizations. Patient satisfaction was assessed through a 35-item closed-question questionnaire. An analysis of stimulating component result indicators for per capital standard financing in PHC organizations based on their achieved outcomes was performed. Results: Among surveyed patients, 54.0% (1.80±1.108) expressed complete satisfaction with medical care, while 59.4% (1.82±1.269) perceived laboratory tests as readily accessible. Notably, males exhibited higher satisfaction levels with medical care and the availability of laboratory tests compared to females. The city polyclinics № 3 and № 14 in Almaty, Kazakhstan, achieved significant performance indicators, resulting in a 1.1-fold increase in the incentive component of per capital funding. Conclusion: Within the framework of compulsory health insurance, primary healthcare organizations in Kazakhstan offer affordable and effective medical care, as attested by surveyed patients and the final result indicators of the polyclinics.
Keywords: healthcare access; health insurance; healthcare quality; primary care